Antibiotic Resistance in Escherichia coli Isolated from Chicken Meat in Traditional Markets of Yogyakarta - Al Farisi, Irsyad; Astuti, Sutan Nur Chamida Tri; Falih, Afifah Nurul; Aji, Oktira Roka; Mardiah, Irma (Universitas Ahmad Dahlan, 2025)
The widespread use of antibiotics in the livestock industry serves both as a preventive measure against diseases and as a feed additive. However, excessive antibiotic use has led to antibiotic resistance, where bacterial exposure to antibiotics renders them resistant to one or more antibiotic agents. This study investigates the presence of antibiotic resistance in Escherichia coli isolated from chicken meat sold in traditional markets in Yogyakarta. An experimental method was employed, using ECB and EMBA media for bacterial isolation. Gram staining was performed to characterize the morphology of E. coli, followed by molecular testing using the uspA gene. Antibiotic susceptibility testing was conducted using the Kirby-Bauer disk diffusion method. A total of 10 chicken meat samples were collected from five traditional markets in Yogyakarta. The antibiotics tested included ampicillin, ciprofloxacin, and chloramphenicol. The results indicated resistance in all 10 isolates. Sample codes G1 and G2 were resistant to all three antibiotics. Samples P1, P2, and L1 exhibited resistance to ampicillin and chloramphenicol, with intermediate resistance to ciprofloxacin. Sample L2 showed resistance to ampicillin, intermediate resistance to ciprofloxacin, and sensitivity to chloramphenicol. Sample B1 exhibited resistance to all antibiotics tested. Sample B2 was resistant to ampicillin and ciprofloxacin, with intermediate resistance to chloramphenicol. Samples K1 and K2 were resistant to ampicillin and chloramphenicol but sensitive to ciprofloxacin. These findings highlight the growing concern of antibiotic resistance in bacterial strains isolated from chicken meat, emphasizing the need for stricter regulations on antibiotic use in the poultry industry.